First Principles Calculations of Electronic, Structural and Optical Properties of (PMMA–ZrO2–Au) and (PMMA–Al2O3–Au) Nanocomposites for Optoelectronics Applications - Hazim, Angham; Abduljalil, Hayder M.; Hashim, Ahmed (Transactions on electrical and electronic materials, 2021)
This study focuses on the quantum mechanical treatment of the geometrical optimization and the electronic structure problems of a nanomaterial PMMA and nanocomposites. The hybrid functional B3LYP/6-31G level of DFT is used to investigate four molecules divided into two groups, they are PMMA as an original basis molecule and (PMMA–Au), (PMMA–Al 2 O 3 –Au), (PMMA–ZrO 2 –Au) nanocomposites as the two group. The DFT calculations have been performed using Gaussian 09 package of programs. The geometrical optimization included both bonds in °A and angles in deg. The calculated electronic properties included the total energy, HOMO and LUMO energies, energy gap, ionization energy, electron affinity, electronegativity, electrochemical hardness, electronic softness and Electrophilic index. The geometrical optimization of PMMA and nanocomposites has been found in good agreement with the experimental data because of its relaxed geometrical parameters. One of the important results was obtain in this study, is the decreasing of the energy gap. This states that these nanocomposites are the nearest to semiconductor due to the both HOMO and LUMO levels become more adjacent. These consequences mention to construct new structures with new electronic properties. All nanocomposites need small energy to become cationdue to ionization potential is decrease with addition nanoparticles to the pure PMMA, but the electronic affinity is an increase with with addition nanoparticles to the pure PMMA. The total ground state energy of the PMMA have largest value of total energy compared for other nanocomposites, where E T decreased with addition nanoparticles to pure PMMA. The hardness decrease with addition nanoparticles to the pure PMMA, therefore all the nanocomposites are softer, and this reduces the resistance of a species to lose electrons. Good relax for the structures of the studied PMMA was obtained theoretically, in which, the angles C–C, C=O and C–H in pure PMMA are remain in the same ranges for other nanocomposites. In general, most of the studied nonocomposites direct electronic transition from the valence to conduction band with wave length lies in the range of solar spectrum. The obtained results showed that the (PMMA–ZrO 2 –Au) and (PMMA–Al 2 O 3 –Au) nanocomposites have huge applications in electronics and photo-electronics fields.